Nadzieja w dyskursie afektywnym Czesława Miłosza - Agnieszka Rydz (Studia Rossica Posnaniensia)
The work aims to discuss the relationship between the vision of hope in Czesław Miłosz’s writing and the need for man to find meaning. The author realizes the theme based on the novel The Issa valley by the Polish Nobel Prize winner. The basic context in this sketch is the logotherapy project of Emanuel V. Frankl, professor of psychiatry and author of the bestseller Man in search of meaning. But another work by Frankl will be recalled here: The will of meaning, because in it the author included the assumptions of logotherapy. Other contexts introduced into this sketch are the cultural theory of emotions (Richard A. Shweder) and elements of the concept of subject (Michel Foucault). According to Miłosz – which results from the analysis of his novels – hope is necessary to find the meaning of existence. There is also an inverse relationship: the lack of hope has as its result a sense of meaningless existence, which can lead the hero of the novel to suicide. For Miłosz, finding the meaning of life, as well as not finding it, is a kind of mystery to which literature can make an approach. At the same time, literature can be something of a medium of meaning.